On vibration isolation of sandwich plate with periodic hollow tube core. (March 2019) - Yu, Gui-Lan; Miao, Hong-Wei
The vibration isolation performance of a PC sandwich plate with periodic hollow tube core is investigated experimentally and numerically. The experiment results reveal that there exist vibration attenuation zones in acceleration frequency responses which can be improved by increasing the number of periods or tuning some structure parameters. The presence of soft fillers shifts the attenuation zone to lower frequencies and enhances the capability of vibration isolation to some extent. Dispersion relations and acceleration frequency responses are calculated by finite element method using COMSOL MULTIPHYSICS. The attenuation zones obtained by experiments fit well with that by simulations, and both are consistent with the band gap in dispersion relations. The numerical and experimental studies in the present paper show that this PC sandwich plate exhibits a good performance on vibration isolation in low frequency ranges, which will provide some useful references for relevant research and potential applications in vibration propagation manipulations.